Appendix sentences that start with the conjunction (waw ("و" in the Qur’anic stories - Zhyan Jamal Ali (Zanco Journal of Humanity Sciences)
The subject of this study came to deal with one of the arts of Arabic rhetoric, which is the appendix style. The appendix is one of the linguistic formulas created by GOD Almighty to contribute to the sequence and harmony of the Qur'anic verses, to give the sentence splendor in depicting the intended meaning, and to contribute to expanding the significance expressed in a concise and eloquent manner. They are sentences, whose meanings are characterized by generality and totality, and they benefit continuity and continuity, and they come to emphasize the causal and its determination in the soul. However, the appendix is a method that cannot be avoided, whether it is prohibition or news. However, the appendix is ​​a method that cannot be cut or deducted from the structure, but rather it is a complementary follower of the meaning, because it always includes the appendix, as it takes others to supplement, like the general for a special reason, and in this study I will shed light on the role of the verbal link (waw   which topped the appendix sentences in the Qur’anic stories, to show the relationship between the appendix and the appendix, and to show the extent of its connection to the appendix and to reveal its meanings that topped the appendix sentences, and whose meaning changes based on what the meaning of the sentence calls, an attempt to reach the purposes and connotations suggest to her.